Profile of Semiquinone Radicals, Phytohormones and Sugars in Pistacia vera L. cv. Kirmizi Development - Iwona Morkunas (MDPI AG, 2021)
The main aim of this study was to investigate metabolic responses of fruits, leaves, and shoots of pistachio trees (Pistacia vera L. cv. Kirmizi) during their development. Electron paramagnetic resonance spectroscopy revealed significant increase in generation of semiquinone radicals in fruits and leaves of pistachio, while the flower cluster thinning application was conducted in relation to the control; especially at the second term of the plant material collection. Moreover, flower abscission caused an increase in the level of phytohormones such as indole-3-acetic acid and abscisic acid in fruits at the first term of fruits sampling. In turn, high-performance liquid chromatography analysis revealed differences both in the profile as well as the contents of soluble sugars detected in pistachio organs. The highest total sugar content was found in fruits of pistachio where the flower cluster thinning application was made early. Total sugar levels were higher also in leaves and shoots of the above-mentioned pistachio plants in relation to the control until the third sampling time. The importance of high levels of fructose in the fruits following the flower abscission was observed. Additionally, analyses of mineral elements in organs showed that copper and phosphorus contents in fruits were higher after the flower abscission in relation to the control. To conclude, our findings signal on contribution of semiquinone radicals, paramagnetic manganese ions, phytohormones, nutrients, and sugars in pistachio organs development on the background of the flower cluster thinning which was applied before fructification.